Primary Small Cell Undifferentiated (Neuroendocrine) Carcinoma of the Maxillary Sinus - Santosh Kumar Yadav; Premalatha Shetty (Case Reports in Dentistry)
Primary small cell neuroendocrine carcinoma (SNEC) of the paranasal sinuses is an extremely rare and distinctive tumor with aggressive clinical behavior. Moreover, SNECs originating in the head and neck region have been reported to be highly aggressive and to have a poor prognosis. This report describes a patient with a maxillary sinus SNEC who was successfully treated with neoadjuvant chemotherapy and concurrent chemoradiotherapy.